Effects of Sweet Bee Venom and Bee Venom on the Heart Rate Variability - Yook Tae-Han; Yu Jung-Suk; Jung Han-Sung (Journal of Pharmacopuncture, 2008)
Objective : In this study, we investigated the effects of Sweet Bee Venom(SBV) and Bee Venom(BV) at a acupoint, HT7(Shinmun) on the Heart Rate Variability(HRV) in the healthy man. And we tried to observe how Sweet Bee Venom and Bee Venom affects on the balance of the autonomic nervous system. Methods : We investigated on 22 heathy volunteers consisted of 10 subjects in SBV group and 12 subjects in BV group. Study form was a randomized, placebo-controlled, double-blind clinical trial. 22 subjects of each group were injected SBV and BV at HT7(Shinmun). And we measured HRV by QECG-3:LXC3203 (LAXTHA Inc. Korea) on 7 times : before and after injection per 5minutes during 30minutes. Results : 1. After SBV injection, Mean-RR was significantly high from 0 to 10 minutes, Mean-HRV was significantly low from 0 to 10 minutes, SDNN was significantly high after 25minutes, Complexity was significantly high from 5 to 10minutes and RMSSD was significantly high from 5 to 10minutes. 2. Complexity of SBV Group significantly decreased from 20 to 25minutes, RMSSD of SBV Group significantly increased from 10 to 15minute and from 20~25minutes, SDSD of SBV Group significantly increased from 10 to 15 minute and from 20~25minutes compared with that of BV group. 3. After SBV injection, Ln(VLF) was significantly from 25 to 30minutes. Conclusions : The results suggest that SBV in heathy adult man tend to activate the autonomic nervous system compared to BV within normal range.